Relating health information literacy self-efficacy to information technology use and health status: A large-scale study of Chinese undergraduates - Fu, Shaoxiong; Chen, Xiaoyu; Deng, Shengli (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2021)
The purpose of this paper is to relate individuals’ health information literacy (HIL) self-efficacy to their information technology (IT) use and health status. Using a large-scale field survey with 6,160 valid respondents from undergraduates in a Chinese university, we found that individuals’ HIL self-efficacy was significantly related to some socio-demographics and lifestyle features, IT use, and health status. Meanwhile, some socio-demographics and lifestyle features and health status help identify low HIL self-efficacy individuals, while moderate daily IT use may improve HIL self-efficacy. Theoretical and practical implications, as well as limitations and future work, are also discussed.